NaSi and Si clathrate prepared on Si substrate. Issue 12 (13th November 2013) - Kume, Tetsuji; Iwai, Yoshiki; Sugiyama, Tomoya; Ohashi, Fumitaka; Ban, Takayuki; Sasaki, Shigeo; Nonomura, Shuichi; Maeda, Yoshihito; Suzuki, Motofumi
Abstract In this study, we attempted to prepare films of Si clathrates (Na8Si46 (Type I) and Nax Si136(Type II)) and NaSi by using Si single crystalline substrates as the Si source. NaSi, which is the precursor of the Si clathrate, was successfully generated as a highly orientated film on the Si substrate, by exposing Na vapor under Ar atmosphere. The NaSi film was then transformed into Si clathrate film of several µm in thickness, by heat treatment (400 °C, 3 h) under vacuum (∼ 10‐4 Pa). Type I and II clathrates were selectively synthesized by using the crystal orientation (100) and (111) of Si substrates, respectively. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)